Choroidal thickness findings in two siblings with nanophthalmos by swept source-OCT: a case report. (December 2017) - Kaneko, Hiroyuki; Shinojima, Ari; Ryusaburo, Mori; Kawamura, Akiyuki; Yuzawa, Mitsuko
Abstract Background We investigated choroidal thicknesses at five sites in two siblings (four eyes) with nanophthalmos using swept-source optical coherence tomography. Case presentation Case 1, a 51-year-old Japanese female with high hyperopia (Right: +20.5 Dioptors, Left: +19.5 Dioptors), had axial lengths of 15.6 mm in both eyes. Case 2, a 55-year-old Japanese male with high hyperopia (Right: +22.5 Dioptors, Left: +22.8 Dioptors), had axial lengths of 14.8 and 14.7 mm in the right and left eyes, respectively. Choroidal thickness was measured at five sites in each eye using swept-source optical coherence tomography; subfoveal, nasal, temporal, superior and inferior (the 4 non-subfoveal sites were measured 3000 µm from the fovea). Conclusion The mean choroidal thickness was 355.8 ± 63.6 μm at the subfoveal, 466.3 ± 85.1 μm at the nasal, 274.8 ± 77.2 μm at the temporal, 396.8 ± 54.6 μm at the superior, and 480.8 ± 66.8 μm at the inferior (mean ± standard deviation) site. Choroidal thickness was maximal at the inferior site. The choroid was thinnest, in diminishing order, at the nasal, superior, subfoveal and temporal sites.